SYNTHESIS AND CHARACTERIZATION OF Mn-DOPED SODIUM POTASSIUM NIOBATE (KNN) THIN FILM - Afiq, H.A.M.; Warikh, A.R.M.; Azlan, U.A.A.; Maziati Akmal, M.H.; Moriga, T. (Journal of Advanced Manufacturing Technology (JAMT), 2024)
The objective of this study is to produce and analyse thin films of Mn-doped potassium sodium niobate (KNN) using the sol-gel process. The purpose is to investigate and find a solution for the issue of high leakage current density that occurs at high electric fields in KNN films. The aim is to improve dielectric and ferroelectric properties by introducing manganese (Mn) dopants at different concentrations ranging from 0.0% to 0.9%, while ensuring that insulation resistance remains satisfactory. X-ray diffraction (XRD) research was utilized to look into the Mn-doped KNN thin films crystalline structure. The production of Mn-doped KNN thin films displays an orthorhombic crystal structure, according to the results of the XRD investigation. The occupancy of KNN thin films is demonstrated by XRD peaks, indicating a successful synthesis. The thin films microstructure and surface morphology were investigated by using field-emission scanning electron microscopy (FESEM). The greatest results for dense grain development and consistent grain size were seen in 0.3% Mn-doped KNN thin films. According to the results of the FESEM and AFM, the cracks were densely coated with thin films of consistent thickness, and they were not supported by the surface data of the KNN thin films. AFM and PFM analysis shows that 0.3% of Mn-doped KNN thin films significant increase on the surface morphology and the value of piezoelectric coefficient.